Implications of 'Africanness' for educational planning in the Republic of South Africa : a qualitative study of educational needs - Stonier, John Lawson (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1996.